Comparative effectiveness and safety of four traditional Chinese medicine injections with invigorating blood circulation, equivalent effect of anticoagulation or antiplatelet in acute myocardial infarction: a Bayesian network meta-analysis - Chen, Jiaping; Shang, Juju; Liu, Hongxu; Li, Xiang; Lai, Xiaolei; Lou, Yan; Zhou, Huiwen (Frontiers in Pharmacology, 2024)
Background: Traditional Chinese medicine injections with invigorating blood circulation (TCMI-IBCs), which have been used as antithrombosis therapies, are widely employed by Chinese clinicians as adjuvant therapy for acute myocardial infarction (AMI). Objective: A bayesian network meta-analysis was conducted to contrast the effectiveness and safety of four TCMI-IBCs in AMI. Methods: Eight Databases were thoroughly searched before December 31, 2023, for randomized controlled trials (RCTs) focusing on the application of TCMI-IBCs combined with conventional treatments (CT) to treat AMI. All-cause mortality (ACM) was the major endpoint. Secondary outcomes included bleeding events, malignant arrhythmia (MA), recurrent myocardial infarction (RMI), left ventricular ejection fraction (LVEF), and adverse events. Stata17.0 and GeMTC software were employed for Bayesian network meta-analysis. Results: A total of 73 eligible RCTs involving 7,504 patients were enrolled. Puerarin injection (PI), Danhong injection (DI), sodium Tanshinone IIA Sulfonate injection (STSI), and Danshen Chuanxiongqin injection (DCI) combined with CT can significantly reduce the occurrence of ACM and improve LVEF in AMI (P＜0.05), while without significant impact on bleeding events or MA (P＞0.05). STSI + CT would be the optimal treatment strategy in lowering RMI and ACM. DI + CT was the most likely to be the optimal strategy in reducing MA occurrence and improving LVEF. CT was likely the most effective strategy in reducing bleeding events. However, DI + CT exhibited the least favorable safety. Conclusion: TCMI-IBCs + CT had potential benefits in the treatment of AMI. STSI + CT showed the most favorable performance in treating AMI, followed by DI combined with CT.